THE VALUE OF ULTRASOUND CRITERIA IN THE DIAGNOSIS OF POLYCYSTIC OVARIAN MORPHOLOGY - Кравченко, Елена Николаевна; Хомутова, Елена Юрьевна; Енгуразова, Эльмира Наильевна (Mother and Baby in Kuzbass, 2021)
Polycystic ovary syndrome (PCOS) is one of the most commonly observed diseases associated with endocrine disorders in women of childbearing age. The prevalence of PCOS is associated with the assessment of the criteria used to recognize this syndrome and the characteristics of the population sample. Early diagnosis of PCOS plays a key role in treating symptoms, improving quality of life and identifying fertility problems, and, in the long term, including metabolic, cardiovascular and psychosocial issues. It remains relevant to search for clear, specific markers of PCOS, allowing the detection of the disease in the early stages of its development. Diagnosis of polycystic ovary syndrome, including with the help of ultrasound, in women of reproductive age is of great social and medical importance. Ultrasonographic findings for the diagnosis of PCOS should be interpreted in conjunction with hormonal studies, in particular with serum AMH levels. Early recognition and an individual approach to the management of patients with PCOS are necessary for the selection of treatment, predicting the course of the disease.